2016
DOI: 10.1080/00325481.2016.1173514
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin in the treatment of patients with type 2 diabetes presenting with high baseline A1C

Abstract: In patients with poorly controlled type 2 diabetes defined as A1C ≥ 9% or ≥ 10%, dapagliflozin provided clinically meaningful improvements in glycemic parameters, body weight, and blood pressure, and was generally well tolerated, making it a good therapeutic option for patients with high A1C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…As reviewed previously in Drugs [4, 5], numerous randomized, double-blind, multicentre, phase 3 trials with dapagliflozin as monotherapy and combination therapy have demonstrated its efficacy in improving glycaemic control and reducing bodyweight and BP in a broad spectrum of patients with T2D, including those with high baseline HbA 1c (≥ 9%) [12] and the elderly (aged ≥ 65 years) [13]. Results from more recent trials, including special populations such as patients with chronic kidney disease (CKD) stage 3A [14], hypertension [15, 16] or CVD [17, 18], are summarized in Tables 1 and 2).…”
Section: Therapeutic Efficacy Of Dapagliflozinmentioning
confidence: 99%
“…As reviewed previously in Drugs [4, 5], numerous randomized, double-blind, multicentre, phase 3 trials with dapagliflozin as monotherapy and combination therapy have demonstrated its efficacy in improving glycaemic control and reducing bodyweight and BP in a broad spectrum of patients with T2D, including those with high baseline HbA 1c (≥ 9%) [12] and the elderly (aged ≥ 65 years) [13]. Results from more recent trials, including special populations such as patients with chronic kidney disease (CKD) stage 3A [14], hypertension [15, 16] or CVD [17, 18], are summarized in Tables 1 and 2).…”
Section: Therapeutic Efficacy Of Dapagliflozinmentioning
confidence: 99%
“…Dapagliflozin is the first SGLT2 inhibitor demonstrated to clearly reduce hemoglobin A 1c (HbA 1c ) and fasting plasma glucose (FPG) in clinical therapy [18,19]. SGLT2 gene expression profiling demonstrated ubiquitous distribution in kidney, colon, and liver [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several systematic reviews and meta-analyses of RCTs reported that SGLT2i as monotherapy were efficacious, reduced body weight and BP, and were well tolerated by T2DM patients [ 48 52 ]. In addition, several RCTs also reported that SGLT2i were associated with clinically meaningful improvements in glycaemic parameters, and a reduction in body weight and BP in patients with baseline A1C ≥ 9% or ≥ 10% [ 53 55 ].…”
Section: Sglt2i and Diabetesmentioning
confidence: 99%